2018
DOI: 10.1097/pas.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation Sequencing Reveals Recurrent Somatic Mutations in Small Cell Neuroendocrine Carcinoma of the Uterine Cervix

Abstract: Small cell neuroendocrine carcinoma (SCNEC) of the uterine cervix is a rare but extremely aggressive tumor. While high-risk human papillomavirus (HPV) is involved at an early stage of oncogenesis in many tumors, additional driving events have been postulated to facilitate the progression of SCNECs. Identification of oncogenic drivers could guide targeted therapy of this neoplasm. Clinicopathologic features of 10 cervical SCNECs are reported. Analyses included immunohistochemical evaluation of p16, p53, synapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 60 publications
5
85
1
Order By: Relevance
“…36,37 In one study, mutations in caretaker tumour suppressors and activating oncogenic mutations (including RB1 in one case) were identified in four of 10 SmCC-Cx cases. 29 Rb-1 loss by immunohistochemistry has been documented in 73% (16 of 21) SmCC-Cx, 38 similar to our study where four of nine (44%) cases exhibited Rb-1 loss. In our cohort, Rb-1 loss was seen only in tumours with PD-L1 expression; however, this association was not statistically significant in this small cohort.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…36,37 In one study, mutations in caretaker tumour suppressors and activating oncogenic mutations (including RB1 in one case) were identified in four of 10 SmCC-Cx cases. 29 Rb-1 loss by immunohistochemistry has been documented in 73% (16 of 21) SmCC-Cx, 38 similar to our study where four of nine (44%) cases exhibited Rb-1 loss. In our cohort, Rb-1 loss was seen only in tumours with PD-L1 expression; however, this association was not statistically significant in this small cohort.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study using targeted next-generation gene sequencing on 10 patients with SmCC-Cx identified recurrent somatic mutations involving the MAPK, PI3K/AKT/mTOR and TP53/BRCA pathways. 29 Similarly, mutations in PIK3CA, one of the most frequently mutated genes in HPV-related cancers, were detected in 18% (eight of 44) of SmCC-Cx in a hotspot-based study. 30 In contrast, a study using whole exome sequencing identified recurrent mutations in five cases of SmCC-Cx, including ATRX, ERBB4 and AKT/mTOR pathway genes NF1, PTEN, RICTOR and TSC1/2, which is akin to neuroendocrine tumours arising in sites unrelated to HPV infection.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Up-to-date one next generation sequence study was performed on small cell neuroendocrine carcinoma of uterine cervix (SCNEC). Deyin Xing et al found oncogenic driver mutations in KRAS, Erb-B2, c-Myc, BCL6 and NOTCH1 in a cohort of 10 Small cell neuroendocrine carcinomas (SCNEC) of the uterine cervix, a rare but extremely aggressive tumour [92]. In addition, in a cohort of large cells neuroendocrine carcinoma (LCNEC), the most relevant molecular alteration was detected in DLL3, a well-known NOTCH canonical ligand.…”
Section: The Role Of Notch Signaling In Nensmentioning
confidence: 99%